Employment and Shared Growth : Rethinking the Role of Labor Mobility for Development - Paci, Pierella; Serneels, Pieter (Washington, DC: World Bank, 2012)
This edited volume brings together the papers presented at the conference, "Rethinking the Role of Jobs for Shared Growth," held in Washington, DC, in June 2006. The common theme is that of mobility in the labor market. As growth is related to sectoral shifts in economic activity, the mobility of labor plays a crucial role in ensuring sustainable growth whose benefits are shared amongst all individuals. The papers in this volume focus on selected priority issues at the frontier of research in the microeconomics of labor markets in developing countries, multi-segmented labor markets, the role of informal employment and self-employment, the effect of worker mobility on income, and the impact of firm dynamics on growth and employment. These are important parts of the puzzle and contribute to a better understanding of the role of employment in the economic development of low-income countries.